Omic insights into various ceftazidime-avibactam-resistant Klebsiella pneumoniae isolates from two southern Italian regions - Bongiorno, Dafne; Bivona, Dalida A.; Cicino, Claudia; Trecarichi, Enrico M.; Russo, Alessandro; Marascio, Nadia; Mezzatesta, Maria Lina; Musso, Nicolò; Privitera, Grete F.; Quirino, Angela; Scarlata, Giuseppe G. M.; Matera, Giovanni; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Ceftazidime-avibactam (CZA) is one of the best therapeutic options available for infections caused by Klebsiella pneumoniae carbapenemase (KPC)-producing bacteria. However, sporadic reports of CZA-resistant strains have been rapidly increasing in patients. Herein, we provide detailed case reports of the emergence of ceftazidime-avibactam resistance to identify their resistome and virulome using genomic molecular approaches. Sixteen isolates were collected from 13 patients at three hospitals in Catania and Catanzaro (Italy) between 2020-2021. Antimicrobial susceptibility was determined by broth microdiluition. The samples included in study were analyzed for resistome, virulome and Sequence Type (ST) using Whole Genome Sequencing (WGS). All strains were resistant to ceftazidime/avibactam, ciprofloxacin, extended-spectrum cephalosporins and aztreonam, 13/16 to meropenem, 8/16 to colistin and 7/16 to fosfomycin; 15/16 were susceptible to meropenem/vaborbactam; all strains were susceptible to cefiderocol. Molecular analysis showed circulation of three major clones: ST101, ST307 and ST512. In 10/16 strains, we found a blaKPC-3 gene; in 6/16 strains, four different blaKPC variants (blaKPC28-31-34-50) were detected. A plethora of other beta-lactam genes (blaSHV28-45-55-100-106-187-205-212, blaOXA1-9-48, blaTEM-181 and blaCTX-M-15) was observed; blaOXA-9 was found in ST307 and ST512, instead blaOXA48 in one out four ST101 strains. With regard to membrane permeability, ompK35 and ompK36 harbored frameshift mutations in 15/16 strains; analysis of ompK37 gene revealed that all strains harbored a non-functional protein and carry wild-type PBP3. There is an urgent need to characterize the mechanisms underlying carbapenem resistance and the intrinsic bacterial factors that facilitate the rapid emergence of resistance. Furthermore, it is becoming increasingly important to explore feasible methods for accurate detection of different KPC enzymes.